2017
DOI: 10.1002/anie.201706602
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects between Atomically Dispersed Fe−N−C and C−S−C for the Oxygen Reduction Reaction in Acidic Media

Abstract: Various advanced catalysts based on sulfur-doped Fe/N/C materials have recently been designed for the oxygen reduction reaction (ORR); however, the enhanced activity is still controversial and usually attributed to differences in the surface area, improved conductivity, or uncertain synergistic effects. Herein, a sulfur-doped Fe/N/C catalyst (denoted as Fe/SNC) was obtained by a template-sacrificing method. The incorporated sulfur gives a thiophene-like structure (C-S-C), reduces the electron localization arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
256
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 432 publications
(266 citation statements)
references
References 42 publications
7
256
0
3
Order By: Relevance
“…[1] In principal, the energy efficiency of rechargeable Zn-air batteries is primarily dominated by their oxygen electrocatalysts on air electrodes, where the oxygen evolution reaction( OER) and oxygen reduction reaction (ORR) alternatelyp roceed for charging and discharging, respectively.U nfortunately,a saresult of their multi-step fourelectron transfer properties, the ORR and OER processes suffer from extremely sluggish kinetics, which leads to very large potential gaps (> 0.85 V) and low energy efficiency for rechargeable Zn-air batteries. [3] However,t he high cost, scarcity,a nd poor stability of the Pt and Ir-based composite catalysts seriously inhibitt heir widespreadu tilization in rechargeable Zn-air batteries. [3] However,t he high cost, scarcity,a nd poor stability of the Pt and Ir-based composite catalysts seriously inhibitt heir widespreadu tilization in rechargeable Zn-air batteries.…”
mentioning
confidence: 99%
“…[1] In principal, the energy efficiency of rechargeable Zn-air batteries is primarily dominated by their oxygen electrocatalysts on air electrodes, where the oxygen evolution reaction( OER) and oxygen reduction reaction (ORR) alternatelyp roceed for charging and discharging, respectively.U nfortunately,a saresult of their multi-step fourelectron transfer properties, the ORR and OER processes suffer from extremely sluggish kinetics, which leads to very large potential gaps (> 0.85 V) and low energy efficiency for rechargeable Zn-air batteries. [3] However,t he high cost, scarcity,a nd poor stability of the Pt and Ir-based composite catalysts seriously inhibitt heir widespreadu tilization in rechargeable Zn-air batteries. [3] However,t he high cost, scarcity,a nd poor stability of the Pt and Ir-based composite catalysts seriously inhibitt heir widespreadu tilization in rechargeable Zn-air batteries.…”
mentioning
confidence: 99%
“…Concurrently, a vital aspect for single or few‐atom motifs to improve the ORR efficiency is to obtain a structural design of the catalysts that enhances the selectivity toward 4e − reduction of O 2 by suppressing the production of H 2 O 2 . It has been shown that under alkaline solutions, the Lewis acidic Fe 2+ active sites can efficiently adsorb and immediately reduce the Lewis basic HO 2 − intermediates through a 4e − process . However in very strong alkaline electrolytes, the active sites from the iron center are fully covered by adsorbed hydroxy species in the inner Helmholtz plane and the solvated O 2 is localized in the outer Helmholtz plane .…”
Section: Iron‐based Electrocatalystsmentioning
confidence: 99%
“…Accordingly, in recent years, there has been an increasing attention devoted to downsizing the transition metal particles into clusters or ultimately into single atoms supported in matrixes consisting of non‐noble‐metal materials . Such single‐ or few‐atom motifs embedded in a conductive matrix have the potential to both deliver a low overpotential at each active site and concurrently be present in large quantities to provide an overall high turnover number and thus a high current density at low potential.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Compared with bulk metal catalysts,a tomically dispersed metal or metal-doped carbon possesses distinct electronic structure and fully exposed active sites,r endering catalytic reactions better reactivity and selectivity. [14] Compared with bulk metal catalysts,a tomically dispersed metal or metal-doped carbon possesses distinct electronic structure and fully exposed active sites,r endering catalytic reactions better reactivity and selectivity.…”
Section: Zuschriftenmentioning
confidence: 99%